2019
DOI: 10.1111/1365-2435.13487
|View full text |Cite
|
Sign up to set email alerts
|

An emerging fungal pathogen is associated with increased resting metabolic rate and total evaporative water loss rate in a winter‐active snake

Abstract: 1. Energy allocation trade-offs associated with mounting metabolically costly immune responses may serve as sublethal mechanisms by which pathogens reduce host fitness. The emergence of cutaneous fungal pathogens, which invade the skin of their host and have the potential to disturb energy and water balance, highlight the importance of host physiology in determining individual-and populationlevel effects of disease. Snake fungal disease (SFD, ophidiomycosis), caused by the fungal pathogenOphidiomyces ophiodiic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…In the current study, metabolism was measured at an ecologically relevant body temperature at or above temperatures associated with behavioral fever in snakes (Burns et al, 1996;Tetzlaff et al, 2017) and consistent with field body temperatures taken from summer-active S. miliarius in central Florida (May et al, 1996). In a study on the costs of coping with ophidiomycosis, afflicted S. miliarius exhibited elevated RMR compared with healthy individuals across three ecologically relevant temperatures (17, 25 and 32°C;Agugliaro et al, 2020). Snakes with ophidiomycosis exhibited a mean metabolic increment of 35% (45% at 17°C, 30% at 25°C, 30% at 32°C), demonstrating that coping costs are detectable across a broad range of body temperatures and potentially higher at lower temperatures.…”
Section: Metabolic Response To Lps Challengementioning
confidence: 53%
See 1 more Smart Citation
“…In the current study, metabolism was measured at an ecologically relevant body temperature at or above temperatures associated with behavioral fever in snakes (Burns et al, 1996;Tetzlaff et al, 2017) and consistent with field body temperatures taken from summer-active S. miliarius in central Florida (May et al, 1996). In a study on the costs of coping with ophidiomycosis, afflicted S. miliarius exhibited elevated RMR compared with healthy individuals across three ecologically relevant temperatures (17, 25 and 32°C;Agugliaro et al, 2020). Snakes with ophidiomycosis exhibited a mean metabolic increment of 35% (45% at 17°C, 30% at 25°C, 30% at 32°C), demonstrating that coping costs are detectable across a broad range of body temperatures and potentially higher at lower temperatures.…”
Section: Metabolic Response To Lps Challengementioning
confidence: 53%
“…Costs associated with immune performance are becoming increasingly appreciated as drivers of energetic tradeoffs (Demas et al, 2012;Downs et al, 2014;Lochmiller and Deerenberg, 2000), and recent studies implicate energetic costs of infection as a proximate mechanism contributing to the impacts of emergent pathogens on individuals and populations (e.g. Agugliaro et al, 2020;Mayack and Naug, 2009;Reeder et al, 2012;Wu et al, 2018). However, for many groups of organisms, immune-associated energetic costs have not been quantified, and the intrinsic and extrinsic factors that impact allocation priorities have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…SFD studies in free ranging and captive snakes have documented behavioral and physiological changes in infected snakes such as lethargy (80) and higher metabolic rates (82). Much of SFD-related mortality is attributed to less frequent foraging and anorexia (30).…”
Section: Discussionmentioning
confidence: 99%
“…SFD studies in free ranging and captive snakes have documented behavioral and physiological changes in infected snakes such as lethargy ( 80) and higher metabolic rates (82).…”
Section: Insights Into Sfd Host Pathology From Gene Expression Datamentioning
confidence: 99%
“…Specifically, snakes with ophidiomycosis have shown a decrease in body condition with increasing severity of infection, but severity was not associated with recapture rate, and severely affected snakes apparently cleared infection [ 54 ]. It was also observed that the resting metabolic rate in this species was increased in ophidiomycosis-positive individuals, which may contribute to declining individual health during the disease process [ 55 ]. An increase in fetal mortality was observed following supplemental feeding of ophidiomycosis-positive gravid females [ 56 ], and a decrease in sex hormones in both positive males and females was observed, indicating subclinical reproductive effects from ophidiomycosis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%